Protocol of a randomised controlled trial in cardiac surgical patients with endothelial dysfunction aimed to prevent postoperative acute kidney injury by administering nitric oxide gas. Issue 7 (4th July 2019) - Marrazzo, Francesco; Spina, Stefano; Zadek, Francesco; Lama, Tenzing; Xu, Changhan; Larson, Grant; Rezoagli, Emanuele; Malhotra, Rajeev; Zheng, Hui; Bittner, Edward A; Shelton, Kenneth; Melnitchouk, Serguei; et al.
Abstract : Introduction: Postoperative acute kidney injury (AKI) is a common complication in cardiac surgery. Levels of intravascular haemolysis are strongly associated with postoperative AKI and with prolonged (>90 min) use of cardiopulmonary bypass (CPB). Ferrous plasma haemoglobin released into the circulation acts as a scavenger of nitric oxide (NO) produced by endothelial cells. Consequently, the vascular bioavailability of NO is reduced, leading to vasoconstriction and impaired renal function. In patients with cardiovascular risk factors, the endothelium is dysfunctional and cannot replenish the NO deficit. A previous clinical study in young cardiac surgical patients with rheumatic fever, without evidence of endothelial dysfunction, showed that supplementation of NO gas decreases AKI by converting ferrous plasma haemoglobin to ferric methaemoglobin, thus preserving vascular NO. In this current trial, we hypothesised that 24 hours administration of NO gas will reduce AKI following CPB in patients with endothelial dysfunction. Methods: This is a single-centre, randomised (1:1) controlled, parallel-arm superiority trial that includes patients with endothelial dysfunction, stable kidney function and who are undergoing cardiac surgery procedures with an expected CPB duration >90 min. After randomisation, 80 parts per million (ppm) NO (intervention group) or 80 ppm nitrogen (N2, control group) are added to the gas mixture. Test gases (N2 or NO) are delivered during CPB and for 24 hours after surgery. The primary study outcome is the occurrence of AKI among study groups. Key secondary outcomes include AKI severity, occurrence of renal replacement therapy, major adverse kidney events at 6 weeks after surgery and mortality. We are recruiting 250 patients, allowing detection of a 35% AKI relative risk reduction, assuming a two-sided error of 0.05. Ethics and dissemination: The Partners Human Research Committee approved this trial. Recruitment began in February 2017. Dissemination plans include presentations at scientific conferences, scientific publications and advertising flyers and posters at Massachusetts General Hospital. Trial registration number: NCT02836899 .